PENGARUH KEBIJAKAN PENGELOLAAN ASET DAN AKUNTABILITAS TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN EMPAT LAWANG - Weni Herlianti; Nensi Yuniarti. Zs; Furqonti Ranidiah; Dinal Eka Pertiwi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the influence of asset management and accountability policies on the quality of financial reports of the Empat Lawang Regency Government. The research method used is a quantitative method using primary data obtained through questionnaires distributed to 53 Empat Lawang Regency Government employees involved in asset management and financial report preparation. Data analysis techniques include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing (t-test and F-test). The results show that asset management policies have a positive and significant effect on financial report quality, while accountability has a positive effect on financial report quality. Simultaneously, asset management and accountability policies have a significant effect on financial report quality with a coefficient of determination (R²) of 0.778, indicating that 77.8% of the variation in financial report quality can be explained by these two variables, while the remaining 22.2% is influenced by other factors outside the study. The conclusion of this study is that the implementation of good asset management policies and increased accountability can improve the quality of financial reports of the Empat Lawang Regency Government. Keywords: Accountability, Asset Management Policy, Financial Report Quality, Local Government